Enhancing the Effectiveness of External Support in Building Tax Capacity in Developing Countries. (Policy Papers; Policy Paper ;, 2016)
This report responds to the February 2016 request from the G20 for the IMF, OECD, United Nations and World Bank Group to: ' ... recommend mechanisms to help ensure effective implementation of technical assistance programs, and recommend how countries can contribute funding for tax projects and direct technical assistance, and report back with recommendations at our July meeting.' The report has been prepared in the framework of the Platform for Collaboration on Tax (the 'PCT'), under the responsibility of the Secretariats and Staff of the four mandated organizations. The report reflects a broad consensus among these staff, but should not be regarded as the officially endorsed views of those organizations or of their member countries.